Insecticides for empty grain bins - Subramanyam, Bhadriraju; Sehgal, Blossom (My University, 2014)
In this column, Blossom Sehgal, a graduate research assistant in the Department of Grain Science and Industry, Kansas State University (KSU), Manhattan, teamed up with Milling Journal’s regular contributor Bhadriraju Subramanyam (Subi), a Don Wilbur Sr. Endowed Professor of Postharvest Protection, Department of Grain Science and Industry, KSU, to explain their key findings from evaluating the effectiveness of two insecticides for treating empty bins.
Keywords: ß-cyfluthrin; Chlorpyrifos-methyl plus deltamethrin; Empty bin treatment